La construcción social de la acción colectiva en el Frente Zapatista de Liberación Nacional - Ayala Varela, Jorge (Universidad Autónoma Metropolitana, 2004)
The traditional vision of social movements had been explained for conflicts about bread, belief, land and death. It uses symbolic strategy named framework that includes symbols, myths, rite, beliefs and visions of the world in order to construct action strategy. The collective actors act in reason of the political opportunities that exist in the environment interchange about winning and environment of action as soon as protestation cycle, where is defining the best way to make the manifestation of their dissatisfaction. In the story of social movements of Mexico, the movement of 68 allowed the opening of political spaces and cultures to different groups, the beginning of the autoritarism, the violation of human rights, the misery and corruption is accorder to actualized the lawsuit of peasant and native groups in the sixty¶s, to shoot up the Chiapas¶ EZLN in 1994. Is the beginning of symbols that is wining back the idea of nation, country, flag, native indent. Like political support and pacific way of EZLN is consolidated in the FZLN, its conflict is directed against the privilege of rich people, the corruption, the absence of democracy and the militarism in Chiapas.This group that was born with participation of the society, is not looking to take the power and search together actions with other forces, like organize strategy.The Social Psychology in order to construction social conceives the knowledge like a community interchange, some incorporated historically in the communication, conflict and negotiation. The meanings is creating in the dialogue and the comprehension forms are negotiated. The language is in part creative of the objects about on reflect and all things we are saying about the world is determinate for the conventions of the speech, the real and the good things is the product of the textual accounts.The constructionist option tries to elaborate theories that could asked for the dominant culture and generated new ways for the social action.